Characteristics of Laser-Remelted Al–Ca–Cu–Mn (Zr) Alloys as a New Material for Additive Manufacturing - Nikolay V. Letyagin; Torgom K. Akopyan; Pavel A. Palkin; Stanislav O. Cherkasov; Anastasiya S. Fortuna; Alexandr B. Lyukhter; Ruslan Yu. Barkov (Journal of Manufacturing and Materials Processing)
In this study, prospects of designing new Al–Ca–Cu–Mn (Zr) alloys for additive manufacturing (AM) were evaluated for the example of laser remelting of thin-sheet rolled products. The new as-cast alloys have a hypereutectic structure containing Al27Ca3Cu7 primary crystals and ultrafine eutectic particles of (Al,Cu)4Ca and Al27Ca3Cu7 phases in equilibrium with the aluminum solid solution. The solid solutions are additionally strengthened by alloying with Mn and micro additions of Zr, which contribute to the formation of coarsening-resistant phases without compromising the manufacturability of the alloys. Laser remelting, which simulates AM-typical solidification conditions, promotes the formation of a pseudoeutectic cellular structure without the occurrence of undesirable primary Al27Ca3Cu7. The size of the dendritic cells and eutectic particles is 10 times smaller (for solidification rates of ~200 K/s) than that of the as-cast state. This structure provides for a higher hardness of the laser-remelted alloy (96 HV) as compared to the as-cast alloy (85 HV). Data for the alloy after 350–400 °C long-term annealing for up to 100 h show that the hardness of the Al–Ca–Cu–Mn–Zr alloys declines relatively slowly by ~7.5% as compared to the Zr-free alloy, whose hardness decreases by ~22%. Thus, one can consider these alloys as a promising candidate for AM processes that require high thermal stability.